Dispensing of very low volumes of ultra high viscosity alginate gels a new tool for encapsulation of adherent cells and rapid prototyping of scaffolds and implants - Gepp, Michael M (BioTechniques, 2009)
We present a tool for dispensing very low volumes (20 nL or more) of ultra high viscosity (UHV) medical-grade alginate hydrogels. It uses a modified piezo-driven micrometering valve, integrated into a versatile system that allows fast prototyping of encapsulation procedures and scaffold production. Valves show excellent dispensing properties for UHV alginate in concentrations of 0.4% and 0.7% and also for aqueous liquids. An optimized process flow provides excellent handling of biological samples under sterile conditions. This technique allows the encapsulation of adherent cells and structuring of substrates for biotechnology and regenerative medicine. A variety of cell lines showed at least 70% viability after encapsulation (including cell lines that are relevant in regenerative medicine like Hep G2), and time-lapse analysis revealed cells proliferating and showing limited motility under alginate spots. Cells show metabolic activity, gene product expression, and physiological function. Encapsulated cells have contact with the substrate and can exchange metabolites while being isolated from macromolecules in the environment. Contactless dispensing allows structuring of substrates with alginate, isolation and transfer of cell-alginate complexes, and the dispensing of biological active hydrogels like extracellular matrix-derived gels